2021
DOI: 10.3390/cancers13112658
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Encapsulation of DNA and Other Biomolecules in HAp Microcalcifications of Human Breast Cancer Tissues by Raman Imaging

Abstract: Microcalcifications are detected through mammography screening and, depending on their morphology and distribution (BI-RADS classification), they can be considered one of the first indicators of suspicious cancer lesions. However, the formation of hydroxyapatite (HAp) calcifications and their relationship with malignancy remains unknown. In this work, we report the most detailed three-dimensional biochemical analysis of breast cancer microcalcifications to date, combining 3D Raman spectroscopy imaging and adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…To assess prognostic potential, we used Raman microscopy, a clinically relevant technique, and focused on the composition of the organic matrix that was specifically associated (colocalized) with the mineral component. This approach was based on (i) the potential for calcifications to capture cancer-informative biological moieties ( 40 ) that might otherwise be mobilized or degraded (i.e., provide a “snapshot” of the organic matrix when they formed) and may even differ compositionally from the surrounding tissue ( 100 ) and (ii) the importance of the organic matrix in physiological and pathological biomineralization ( 14 , 101 ). We focused on the Raman C-H stretching spectral region (2800 to 3100 cm −1 range), which exhibits an enhanced signal strength relative to the “fingerprint” region, and a concordant increased potential for practical clinical applications ( 102 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess prognostic potential, we used Raman microscopy, a clinically relevant technique, and focused on the composition of the organic matrix that was specifically associated (colocalized) with the mineral component. This approach was based on (i) the potential for calcifications to capture cancer-informative biological moieties ( 40 ) that might otherwise be mobilized or degraded (i.e., provide a “snapshot” of the organic matrix when they formed) and may even differ compositionally from the surrounding tissue ( 100 ) and (ii) the importance of the organic matrix in physiological and pathological biomineralization ( 14 , 101 ). We focused on the Raman C-H stretching spectral region (2800 to 3100 cm −1 range), which exhibits an enhanced signal strength relative to the “fingerprint” region, and a concordant increased potential for practical clinical applications ( 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium and microcalcifications composed of the magnesium-bearing calcium phosphate phase, whitlockite [Ca 18 (Mg) 2 (HPO 4 ) 2 (PO 4 ) 12 ] ( 37 ), have received attention, but association with malignancy is debated ( 29 , 33 , 38 , 39 ). Although potentially the most direct line to cancer and host biology, less is known about the organic matrix: Classes of biomolecules have been identified within calcifications ( 28 , 40 ), and the organic matrix-to-mineral ratio was shown to be relatively increased in malignant calcifications, particularly in DCIS ( 27 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microcalcifications, considered as one of the first indicators of suspicious cancerous lesions were studied by Marro et al [ 100 ]. Tissue sections of 26 patients with infiltrating ductal and lobular carcinomas with microcalcifications screened previously by mammography were subjected to Raman spectroscopy and multivariate curve resolution (MCR) combined with PCA analysis.…”
Section: Cellular and Tissue Diagnosticsmentioning
confidence: 99%
“…Tissue sections of 26 patients with infiltrating ductal and lobular carcinomas with microcalcifications screened previously by mammography were subjected to Raman spectroscopy and multivariate curve resolution (MCR) combined with PCA analysis. They demonstrated the spatial distribution of DNA, lipids, proteins, cytochrome C and polysaccharides found in microcalcifications and showed that DNA is naturally encapsulated or adsorbed in calcifications present in invasive cancer tissues [ 100 ].…”
Section: Cellular and Tissue Diagnosticsmentioning
confidence: 99%
“…Up to date, the standard method to quantify pigments in the skin is the High-Performance Liquid Chromatography (HPLC) method, which is a chemical degradative method by which the sample is homogenized, and the pigment localization is not possible [ 27 , 28 ]. To achieve a non-invasive quantification and localization, the Multivariate Curve Resolution-Alternating Least Squares (MCR-ALS) method is proposed, as it enables us to obtain the concentration and spatial distribution of molecular components in tissue samples from complex Raman spectral images [ 17 , 29 , 30 ]. Specifically, it was used in the past to study the different skin constituents in tissue sections [ 25 ] or the permeation of retinol in the skin [ 31 ].…”
Section: Introductionmentioning
confidence: 99%